The Effect of Maize-Cowpea Blends on Complementary Food Nutritional Quality (Global Journal of Science Frontier Research, 2016)
The study was conducted with the objective of improving Food nutritional quality in Complementary food through Maize-Cowpea Blends. Maize (Melkassa 7) and two cowpea varieties (Asebot and Bole) were collected from Melkassa Agricultural Research Center. 100 seed weight, volume and density measure of two cowpea varieties were done. Sample preparations were done after cleaning, soaking, dehulling (cowpea), milling, and sieving. Proximate composition analyses were done for grains. And a 25.07%, 21.20% and 10.14% protein contents; 3.71%, 2.61% and 1.01% ash content were observed on Asebot, Bole and Melkassa 7 (Maize) respectively which are significantly different at P
Keywords: anti-nutrient; complementary foods; cowpea fortification; fermentation; steamed cowpeas